Legal Analysis of Land Certificate Legality (SKT) Towards Uncertified Land in Land Sale and Purchase - Mi’rajiah, Dessy; Sri Darmadi, Nanang (Jurnal Konstatering, 2024)
This study aims to analyze: 1) The legality of Land Certificate (SKT) for uncertified land in land sale and purchase. 2) The legal existence of land certificate as proof of ownership of land rights. This type of research is normative legal research. The approach method in this study is the statute approach. The type and source of data in this study are secondary data obtained through literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1) The legality of Land Certificate (SKT) for uncertified land in land sale and purchase in Indonesia has significant limitations. Although the SKT is administratively recognized and can be used as proof of physical control over land, this document does not have the same legal force as a land title certificate issued by the National Land Agency (BPN). In the context of land sales and purchases, the use of SKT as proof of ownership poses legal risks, especially in the event of a dispute, because the SKT does not provide a guarantee of legal ownership and is formally recognized by law. In order to achieve legal certainty and protect the rights of all parties involved in the transaction, the land title certificate remains the only document that is legally recognized as proof of ownership in land sales and purchases. Therefore, it is important for the parties in a land sale and purchase transaction to ensure that the land being traded has a valid certificate, in order to avoid potential legal problems in the future. 2). The legal existence of the Land Certificate (SKT) as proof of land ownership in Indonesia is recognized in the administrative and physical control context, especially in areas where land registration has not been optimal. SKT is often used by the community as proof of land ownership and for administrative purposes, however, the legality of SKT is limited because this document does not have the same legal force as a land title certificate issued by the National Land Agency (BPN). In land disputes or formal legal processes, land certificates are prioritized as proof of legal ownership.